Sociology by Teachers, Senior Students and Professional Master Students for Teaching - Serjanaj, Aida (European Journal of Multidisciplinary Studies, 2016)
This research is about the role of sociology according to literature, my experience and a questionnaire. The result about it is that the majority of the respondent’s estimate about sociology. The answers are connected mostly with the impact of sociological knowledge in making them more courageous in certain situations, defining their individual characteristics, seeing what type of individual they are, discovering new things that they wish and possibly use them, analyzing all the phases of the personal development, making them more optimistic, braver, and more communicative in many aspects, knowing themselves better and make a challenge to it, knowing your best friend better, creating a new concept on them, their character and behavior, you know yourself better, life experience has learned me much more; learning by doing, learning from mistakes, learning different cultures of living, etc. Study sociology is very important. It must be a compulsory subject at our pre-university curriculum.
Keywords: sociology, value, personal development